2017
DOI: 10.1111/jpm.12369
|View full text |Cite
|
Sign up to set email alerts
|

Families’ experiences of involvement in care planning in mental health services: an integrative literature review

Abstract: Introduction Mental health service policy stipulates that family carers be involved in care planning. Aim To identify families' experiences of care planning involvement in adult mental health services. Method An integrative review where electronic databases and grey literature were searched for papers published between 01 January 2005 and 10 February 2016. Results Fifteen papers met the inclusion criteria. Thematic analysis generated three themes: (1) families' experience of collaboration, (2) families' percep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(107 citation statements)
references
References 55 publications
4
100
1
2
Order By: Relevance
“…Consistent with previous reviews (Doody et al, ; Lamore, Montalescot, & Untas, ), this review demonstrated that families are often uninvolved in SDM, although they supported treatment decisions. Because most consumers preferred family involvement, it is recommended to provide a range of approaches to engage families in SDM.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consistent with previous reviews (Doody et al, ; Lamore, Montalescot, & Untas, ), this review demonstrated that families are often uninvolved in SDM, although they supported treatment decisions. Because most consumers preferred family involvement, it is recommended to provide a range of approaches to engage families in SDM.…”
Section: Discussionsupporting
confidence: 87%
“…Although several SDM models explicitly mention the involvement of families or carers (Charles et al, 1997;Légaré et al, 2011), limited interventions explicitly facilitated their involvement (Stomski & Morrison, 2018). Recent studies note the preference of consumers' families to be involved in decisions regarding the consumers' treatment and care planning because they believe that they could contribute to the recovery of the consumer (Doody, Butler, Lyons, & Newman, 2017;Stomski & Morrison, 2018). Families who are involved in daily care do inevitably influence decision-making during and outside consultations (Laidsaar-Powell et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar data are extrapolated, reduced, and categorized for analysis into themes (Doody et al . ). Despite criticism that integrative reviews may lack rigour and introduce bias, they can directly address clinical practice and policy enquiries (Whittemore & Knafl ).…”
Section: Methodsmentioning
confidence: 97%
“…It should also describe the strategies and resources to achieve these outcomes and should give clear criteria for assessing the satisfaction and outcomes of care for the consumer (Bee et al 2015a;McHugh & Byrne 2012). However, the research indicates that mental health service staff often fail to develop meaningful well thought out care plans with consumers (Bee et al 2015a;Bee et al 2015b;Doody et al 2017;Stomski et al 2017). Consumers and their carers have expressed dissatisfaction with a lack of therapeutic engagement in mental health services (McAllister et al 2019;Rydon 2005;Tee et al 2007;Theodoridou et al 2012;Walsh & Boyle 2009), and that they want strengthbased approaches based on concepts of recovery (Dobie, Bulla & Swanke 2010;Henderson et al 2010;Rose 2003).…”
Section: What Is the Problem And Why Are Mental Health Care Plans Neementioning
confidence: 99%